Evolutionary adaptation to aquatic lifestyle in extinct sloths can lead to systemic alteration of bone structure. Issue 1878 (16th May 2018) - Amson, Eli; Billet, Guillaume; de Muizon, Christian
Abstract : Through phenotypic plasticity, bones can change in structure and morphology, in response to physiological and biomechanical influences over the course of individual life. Changes in bones also occur in evolution as functional adaptations to the environment. In this study, we report on the evolution of bone mass increase (BMI) that occurred in the postcranium and skull of extinct aquatic sloths. Although non-pathological BMI in postcranial skeleton has been known in aquatic mammals, we here document general BMI in the skull for the first time. We present evidence of thickening of the nasal turbinates, nasal septum and cribriform plate, further thickening of the frontals, and infilling of sinus spaces by compact bone in the late and more aquatic species of the extinct sloth Thalassocnus . Systemic bone mass increase occurred among the successively more aquatic species of Thalassocnus, as an evolutionary adaptation to the lineage's changing environment. The newly documented pachyostotic turbinates appear to have conferred little or no functional advantage and are here hypothesized as a correlation with or consequence of the systemic BMI among Thalassocnus species. This could, in turn, be consistent with a genetic accommodation of a physiological adjustment to a change of environment.